Molecular Docking Analysis of Family Fabaceae Phytochemistry to Estrogen Receptor Alpha Compared to Tamoxifen in Breast Cancer - Ega Caesaria Pratama Putra; Riza Novierta Pesik; Ratna Kusumawati (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Breast cancer is the second most common cancer.Estrogen is the risk factor of breast cancer. Estrogen receptor ? is expressed by 50-80% of breast cancer. The mechanism of estrogen is mediated by estrogen receptor ? and estrogen receptor ?. Tamoxifen is a selective estrogen receptor modulators (SERMs) that can be bound to the estrogen receptor ?, therefore prevent bonding between estrogen and estrogen receptor ?. Methods: This research used molecular docking analysis of family Fabaceaes Phytochemistry as an inhibitor of estrogen receptor ? activation. This study was observational bioinformatics study to observe interaction between family Fabaceaes phytochemistry and estrogen receptor?. Molecular docking analysis observed binding energy and binding location. This virtual screening analysis was done using PyRx, AutoDock Vina, PyMOL, Open Babel, and UCSF Chimera. Results: We obtained 471 Family Fabaceaes phytochemistry from database, only five compounds that have equal or lower binding energy compared with tamoxifen, that compound werebeta-amyrine (9.6 KJ/Mol), obovatin( 9.6 KJ/Mol), erythrabyssin II (9.6 KJ/Mol), Cajaflavanone (10.2 KJ/Mol), and tomentosanol E (10.5 KJ/Mol). The visualization of binding location analysis showed that only cajaflavanone which have relatively similar binding site location with tamoxifen. Conclusions: Cajaflavanone have a similar characteristic with tamoxifen, and have a potency to be used as partial antagonist of estrogen receptor alpha in breast cancer based molecular docking analysis. However, In vitro and In vivo researchneeded to determine the effectiveness. Keywords: Breast Cancer, Molecular Docking, Fabacea, Tamoxifen, Estrogen Receptor ?